A chicken like a Leviathan? Monsters from a transgenic art (Itinera, 2023)
With his work, the Belgian artist-scientist Koen Vanmechelen poses a challenge to Aesthetics, which does not have the parameters to evaluate it. His artistic experience, which I would drop under the new name of Hybrid-art or Genetic-art, comes from a studied genetic manipulation of animals. If from an artistic point of view the results may apparently have data of continuity with Flemish culture, the Wunderkammers aesthetic effect and experiences such as those of Damien Hirst, the type of scientific research that accompanies it is unique. Vanmechelen, in fact, taxidermizes animals (mainly chickens) born from crosses not previously existing in Nature. The DNA of the animals born from these crosses, now in the XXIIth generation, is part of the “Cosmopolittan Chicken Project” started in 1999 and is aimed at demonstrating that greater biodiversity favors the improvement of the species. Upon their death, these “unique animals” or monsters become works of art in compositions that, historically, we would have framed in the aesthetic terms of the monstrous or the grotesque.
Keywords: Vanmechelen, contemporary art, genetic transformations, Foucault.